Cerebral Revascularization for the Management of Symptomatic Pure Arterial Malformations - Lu, Xiaocheng; Fang, Xinggen; Huang, Yabo; Zhou, Peng; Wang, Zhong; Brinjikji, Waleed; Chen, Gang (Frontiers in Neurology, 2021)
Background: Pure arterial malformations (PAMs) are extremely rare abnormalities defined as dilated, overlapping, and tortuous arteries with a coil-like appearance in the absence of venous components. Over the last half century, only seven published reports have described cases of patients with PAM who received treatment. Methods: Here, we report two cases of women with PAMs who received surgical treatment, and we present a systematic review of the literature. We searched the PubMed, Embase, Web of Science, and Medline databases (up until Oct 1 2021) for relevant publications. We used independent-samples t-tests and Fisher’s exact tests to compare continuous and categorical characteristics between the available cases, respectively. Results: Our first patient was a 43-year-old woman with a PAM of the left internal carotid artery (ICA), who received an ICA-RA(radial artery)-M2 bypass. A post-operative digital subtraction angiography (DSA) revealed the disappearance of the left ICA PAM without ischemic events during follow-up. The second patient was a 53-year-old woman with PAMs of the right ICA and posterior cerebral artery. The P1 lesion was treated by proximal occlusion combined with a superficial temporal artery-P2 bypass. During the 12-month follow-up period, the size of the PAM decreased significantly as indicated by a post-operative DSA and showing the absence of hemorrhages. Our systematic review including 56 PAMs shows that reported PAMs were more common in the anterior circulation (33/56, 58.9%) than in the posterior circulation (11/56, 19.7%). Bilateral PAMs were more liked to affect bilateral anterior cerebral arteries (ACA) (ACAbilateral vs. ACAunilateral: 63.6% vs. 26.2%, p=0.02). In addition, PAMs involving the anterior circulation were likely to affect the multiple arteries (anteriormulti vs. posteriormulti: 30.3% vs. 0.0%, p=0.038). Conclusion: We found very few reports of treated PAMs, further studies with large sample sizes and long follow-up periods are required to explore the appropriate treatment strategy of PAMs.